Alterations in bacterial community dynamics from noncancerous to Gastric cancer - Peng, Xuan; Yao, Siqi; Huang, Jing; Zhao, Yiming; Chen, Hao; Chen, Liyu; Yu, Zheng (Frontiers in Microbiology, 2023)
Gastric microbiome has been shown to contribute to gastric carcinogenesis, understanding how alterations in gastric microbiome is helpful to the prevention and treatment of gastric cancer (GC). However, few studies have focused on the change of microbiome during the gastric carcinogenesis. In this study, the microbiome of gastric juice samples from healthy control (HC), gastric precancerous lesions (GPL) and gastric cancer (GC) was investigated by 16S rRNA gene sequencing. Our results showed that the alpha diversity of patients with GC was significantly lower than other groups. Compared to other groups, some genera in GC group were shown to be up-regulated (e.g., Lautropia and Lactobacillus) and down-regulated (e.g., Peptostreptococcus and Parvimonas). More importantly, the emergence of Lactobacillus was closely related to the occurrence and development of GC. Moreover, the microbial interactions and networks in GPL exhibited higher connectivity, complexity and lower clustering property, while GC showed the opposite trend. Taken together, we suggest that changes in the gastric microbiome are associated with GC and perform a key function in maintaining the tumor microenvironment. Therefore, our findings will provide new ideas and references for the treatment of GC.